2006
DOI: 10.1016/j.intimp.2006.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in maternal and fetal nicotine distribution after maternal administration of monoclonal nicotine-specific antibody to rats

Abstract: Vaccination against nicotine to elicit the production of nicotine-specific antibodies is a potential treatment for tobacco addiction which reduces nicotine distribution from serum to brain. Vaccination of pregnant rats also reduces the distribution of maternally-administered nicotine to fetal brain. Whether this is due to maternal antibody reducing the transfer of nicotine from mother to fetus, or to fetal antibody altering the distribution of nicotine within the fetus, is not clear. In the current study, pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Groups of 12 rats were anesthetized and received 36 mg/kg of Nic311 or nonspecific IgG control. This Nic311 dose has been shown to alter nicotine distribution to approximately the same extent as active immunization with 3′-AmNic-rEPA [34]. Rats were studied one day later, to allow sufficient time for distribution of Nic311 [25], by placing the unanesthetized animals in the WBE unit for 2 hr with smoke parameters as noted above.…”
Section: Methodsmentioning
confidence: 99%
“…Groups of 12 rats were anesthetized and received 36 mg/kg of Nic311 or nonspecific IgG control. This Nic311 dose has been shown to alter nicotine distribution to approximately the same extent as active immunization with 3′-AmNic-rEPA [34]. Rats were studied one day later, to allow sufficient time for distribution of Nic311 [25], by placing the unanesthetized animals in the WBE unit for 2 hr with smoke parameters as noted above.…”
Section: Methodsmentioning
confidence: 99%
“…Although non-nicotine tobacco smoke constituents have been reported to impact fetal brain development [ 11 ], nicotine alone is likely the major contributor to the harmful effects of maternal tobacco use on their offspring. Animal studies have shown that nicotine readily crosses the placental barrier to interact with receptors widely distributed throughout the fetus and richly expressed in the fetal brain [ 12 , 13 ]. These nAChRs are functional [ 14 ] and are upregulated by maternal nicotine intake [ 15 ].…”
Section: Prenatal Nicotine Exposurementioning
confidence: 99%
“…Another advantage is that anti-PCP and anti-METH mAbs do not seem to cross blood-organ barriers such as the brain and testis to any great extent, but they do effectively remove PCP and METH from these organs (Proksch et al, 2000;Laurenzana et al, 2003a). This redistribution of target drug out of brain tissue is the mechanism of action for the neuroprotection mediated by these antiaddiction mAb medications (Laurenzana et al, 2003b;Keyler et al, 2006;Pentel et al, 2006). These findings suggest the potential for similar effects at the maternal blood-brain barrier, fetal blood-brain barrier, and blood-placental barrier, as suggested by studies in nearterm, nicotine-treated pregnant rats (Keyler et al, 2005a,b).…”
Section: Introductionmentioning
confidence: 99%